Kajian Yuridis Terhadap Pembagian Harta Warisan Menurut Hukum Waris Perdata dengan Hukum Waris Islam - Krisnawati, Ferryani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Inheritance law in Indonesia is divided into three, namely Islamic inheritance law, civil inheritance law and customary inheritance law. area. Each inheritance law is different regarding the heirs, the method of distribution and also the legal basis. Inheritance law is one part of civil law as a whole and a small part of family law. This research examines inheritance according to the Civil Code and Islamic law, the regulations are different between civil inheritance law and Islamic inheritance law. In the distribution according to Islamic inheritance law, the portions are clearly regulated in Surah An-Nissa, whereas according to the Civil Code, the number of heirs is seen. So the distribution of inheritance is different and this is the subject of research. This research is a Normative Juridical approach, namely an approach carried out based on primary law by examining theories, concepts, legal principles and statutory regulations related to research. Research specifications are analytical descriptions.